Mindfulness and physical activity: psychometric properties of the state mindfulness scale for physical activity - Bayköse, Nazmi; Arı, Çagrı; Ceylan, Gizem (INT JOURNAL LIFESCIENCE & PHARMA RESEARCH, 2021)
This study aims to test the validity and reliability of the Turkish version of the "State Mindfulness Scale for Physical Activity" developed by Cox, Ullrich-French, and French(1). The research group consists of individuals who study in dance courses in the Cankaya district of Ankara. A total of 217 individuals, 53.5% female (n=116), 46.5% male (n=101), participated in the study voluntarily. The average age of the individuals participating in the study was determined as 31.42 +/- 8.93. n addition, the participants stated that they had continued their dance activities for an average of 4.60 +/- 5.14 years. Data obtained from the research; a) "Personal Information Form" prepared by the researchers, b) "State Mindfulness Scale for Physical Activity" developed by Cox, Ullrich-French and French(1), and c) Lau et al.(2) and adapted to Turkish by Sahin and Kokdemir(3) using the "Toronto Mindfulness Scale." The validity of the mindfulness scale for physical activity was examined by confirmatory factor analysis and concurrent validity. The findings showed that the Turkish adaptation of the state mindfulness scale for physical activity had good psychometric properties to determine physical activity participants' state mindfulness.
Keywords: Mindfulness; Physical activity; State mindfulness